A simplified severity score for acute asthma exacerbation. (15th July 2013) - Dankner, R.; Olmer, L.; Ziv, A.; Bentancur, A. G.
Abstract: Background : To evaluate a simplified severity score designed to facilitate decision making in the Emergency Department (ED) regarding hospital admission of young adult patients with acute asthma exacerbation (AAE). Methods : All AAE-related ED encounters during two calendar years of patients aged 17–35 years were retrospectively classified as "mild", "moderate" or "severe", according to vital and readily available signs and symptoms, including pulse rate, presence of respiratory wheezes, rales or prolonged expirium, oxygen saturation, and the use of accessory muscles, measured upon arrival to the ED. All medical records of ED and hospital admissions were reviewed for treatment and outcomes. Results : During the study period, 723 AAE-related ED encounters were recorded among 551 asthma patients. Of them, 35.0% were classified as "mild", 37.9% "moderate" and 27.1% "severe". For increasing levels of AAE severity, hospital admission rate increased (11.5%, 42.0%, 61.2%, respectively, p < 0.001). Adjusting for age and sex, odds ratios for hospitalization were 12.2 (95% CI: 7.5–19.9) and 5.6 (95% CI: 3.5–8.9) for the "severe" and "moderate" categories, respectively, compared to the "mild" category. "Mild" asthma patients also had shorter length of hospital stay and none required mechanical ventilation or died during hospitalization. Conclusion : The simplified asthma severity score requires no additional tests or costs in the ED, and could facilitate the decision of whether to hospitalize or discharge adult AAE patients. Prospective validation of this tool is needed.